Tectonic evolution and stress field of the Kymi-Aliveri basin, Evia island, Greece - KOKKALAS, S. (Bulletin of the Geological Society of Greece, 2001)
Stress and strain analysis has been used to reconstruct the post-Oligocene geodynamics of the Kymi-Aliveri basin: The Kymi-Aliveri basin occupies the footwall of the Kymi-Thrust, which formed during the Middle Miocene as a large transpressional structure in the late orogenic stages of the Hellenides. Subsequently, in the Upper Miocene the shape of the basin was strongly modified by an orthogonal system of NE and NW trending normal faults as a result of post orogenic collapse. In the Pliocene and Pleistocene time the basin is a part of the back arc basin, which developed behind the Hellenic Arc. WNW trending normal faults and reactivated faults characterized this tectonic phase.